Initiation of Basal Insulin Analog Treatment for Type 2 Diabetes and Reasons Behind Patients’ Treatment Persistence Behavior: Real-World Data from Germany - Moennig, Elisabeth; Perez-Nieves, Magaly; Hadjiyianni, Irene; Cao, Dachuang; Ivanova, Jasmina; Klask, Ralf (Experimental and Clinical Endocrinology & Diabetes, 2018)
Background Poor treatment persistence can affect the real-world effectiveness of insulin therapy. A cross-sectional online survey in 942 patients with type 2 diabetes from 7 different countries evaluated patient experience when initiating basal insulin and the reasons behind insulin persistence patterns. Here, we report the quantitative results for the subset of patients from Germany.Methods Adults with type 2 diabetes who had initiated basal insulin during the last 3–24 months, identified from market-research panels, participated in the survey. Patients were asked if they had ≥7-day gaps in basal insulin treatment, and were then classified as “continuers” (no gap since starting insulin), “interrupters” (≥1 gap within the first 6 months after starting insulin and subsequently restarted insulin), or “discontinuers” (stopped insulin within the first 6 months after starting and had not restarted at the time of the survey). For each country, 50 participants were planned per persistence category. Enrollment ended if the target quota was reached or enrollment plateaued. Data were analyzed overall and separately for each persistence cohort.Results The 131 participants from Germany included 55 (42.0%) continuers, 50 (38.2%) interrupters and 26 (19.9%) discontinuers. The most common motivations to initiate basal insulin therapy were encouragement by physician or other healthcare provider (HCP; 54.2%) and expectation to improve glycemic control (42.0%). More than 95% of participants received training before and during insulin initiation (considered as helpful by 81.7%); most (67.2%) preferred in-person training. Continuers more frequently felt that insulin would help to manage diabetes and that their own views were considered when initiating insulin, they reported less concerns and challenges before and during insulin initiation than interrupters or discontinuers. The most common motivations to continue basal insulin were improved glycemic control (72.7%), improved physical well-being (49.1%), and instruction by physician or other HCP (45.5%). The most common reasons contributing to interruption/discontinuation were perceived weight gain (52.0%/50.0%), hypoglycemia (22.0%/38.5%), and potential adverse effects (30.0%/26.9%).Conclusions Quality interactions between physicians or other HCPs and their patients before and during the initiation of basal insulin may help to manage patient expectations and to improve persistence to insulin therapy.
Keywords: type 2 diabetes; basal insulin; insulin analog; treatment persistence; treatment patterns; Germany